2020
DOI: 10.3389/fmicb.2020.01429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acetamiprid Biodegradation by the Microbial Consortium ACE-3 Enriched From Contaminated Soil

Abstract: Microbial consortia are ubiquitous in nature and exhibit several attractive features such as sophisticated metabolic capabilities and strong environmental robustness. This study aimed to decipher the metabolic and ecological characteristics of synergistic interactions in acetamiprid-degrading consortia, suggesting an optimal scheme for bioremediation of organic pollutants. The microbial consortium ACE-3 with excellent acetamiprid-degrading ability was enriched from the soil of an acetamiprid-contaminated site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Subsequently, the consortia were resuspended in sterilized MSM, supplemented with 40% glycerin, resulting in a final cell concentration of approximately 10 8 cells/ml. The inocula were then cryopreserved at −80°C for subsequent experiments and long-term usage ( Xu et al, 2020 ; Pang et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the consortia were resuspended in sterilized MSM, supplemented with 40% glycerin, resulting in a final cell concentration of approximately 10 8 cells/ml. The inocula were then cryopreserved at −80°C for subsequent experiments and long-term usage ( Xu et al, 2020 ; Pang et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 48 h of incubation, at 200 mg/L, about 70% degradation of acetamiprid was achieved. The degradation of thiamethoxam was investigated in municipal wastewater, and the microbial action accelerated dissipation by UV light to degrade acetamiprid in the contaminated environment, a bacterial strain ACE-3 was isolated from soil, and results indicated that this strain was able to degrade acetamiprid entirely at the initial concentration of 50 mg/L within 144 hours in a broad range of environmental conditions such as pH (6–8) and temperature (20–42 °C) ( Peña et al, 2011 ; Xu et al, 2020 ).…”
Section: Potential Microorganisms For Neonicotinoid Degradation and Their Metabolic Pathwaysmentioning
confidence: 99%
“…The existence and activity of an appropriate microbial consortia is one of the critical components that will affects bioremediation success (Kebede et al, 2021). A microbial consortium is any two or more microbial communities of distinct species or genera acting synergistically in a complicated system (Xu et al, 2020) which can be natural or artificial. For enhanced bioremediation of soil contaminants, a microbial consortium can be more advantageous than a single strain in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
“…The development and use of microbial consortia for the bioremediation of soil contaminants still has numerous obstacles and knowledge gaps. According to Xu et al (2020) the development of effective and stable microbial consortia from natural or contaminated soils involves characterizing and optimizing their metabolic pathways and interactions involved in pollutant degradation, evaluating and enhancing the bioavailability and biodegradability of soil pollutants by microbial consortia, and assessing and monitoring the ecological effects and risks of introducing microbes.…”
Section: Introductionmentioning
confidence: 99%